MANAJEMEN PEMBELAJARAN INOVATIF BERBASIS BERMAIN-AKTIF DAN BERDIFERENSIASI (Studi Kasus Kendala Strategi Pembelajaran Guru Di TKIT Al-Hasan Gowa-Sulawesi Selatan) - St Marwana Aisyah Marwa; Miftahurrahma Kaharuddin; Herman; Syamsuardi (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2026)
Innovative and differentiated learning is an important approach in Early Childhood Education (PAUD) because every child has different learning needs, interests, and abilities. This study aims to describe the implementation of innovative and differentiated learning, identify obstacles faced by teachers, and analyze efforts to improve the quality of learning at TKIT Al Hasan, Gowa Regency. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of two PAUD teachers at TKIT Al Hasan. The results showed that teachers have implemented innovative learning through activities such as playing, singing, storytelling, role-playing, and environmental exploration. Differentiated learning has begun to be implemented through mentoring and assignments tailored to children's abilities, although it has not been implemented optimally. Obstacles encountered include learning media, teacher preparation time, a large number of students, and teachers' limited understanding of differentiated learning. In addition, child development assessments have not been systematically documented. The learning environment at TKIT Al Hasan is quite safe, comfortable, and conducive, but still requires the development of more varied learning media and facilities. Therefore, it is necessary to improve teacher competency through training, workshops, mentoring, and optimization of learning facilities so that the implementation of innovative and differentiated learning can run more effectively and in accordance with the developmental needs of early childhood.